Well, first, the equation that you are looking for is Y = MX + B. To find B, look at the first dot on the Y-axis. It starts at positive 3, so, you know your equation will end with +3. Next, to find MX, start at the either dot, and find the Rise/Run. In this particular equation, the rise is 1, and, the run is -2, because it's going backwards (negative line). Meaning, the line's equation would be, f( x )= -1/2x + 3.
Answer:
Jake's error in step 3
Step-by-step explanation:
we have
![x^{2} -6x+5=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-6x%2B5%3D0)
Complete the square
step 1
Group terms that contain the same variable, and move the constant to the opposite side of the equation
![x^{2} -6x=-5](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-6x%3D-5)
step 2
Complete the square. Remember to balance the equation by adding the same constants to each side
![x^{2} -6x+9=-5+9](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-6x%2B9%3D-5%2B9)
![x^{2} -6x+9=4](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-6x%2B9%3D4)
step 3
Rewrite as perfect squares
![(x-3)^{2}=4](https://tex.z-dn.net/?f=%28x-3%29%5E%7B2%7D%3D4)
Jake's error in step 3
He placed 6 instead of 3 in the left side
step 4
take square root both sides
![\sqrt{(x-3)^2} =\sqrt{4}](https://tex.z-dn.net/?f=%5Csqrt%7B%28x-3%29%5E2%7D%20%3D%5Csqrt%7B4%7D)
step 5
![(x-3)=\pm2](https://tex.z-dn.net/?f=%28x-3%29%3D%5Cpm2)
step 6
![x=3\pm2](https://tex.z-dn.net/?f=x%3D3%5Cpm2)
step 7
x=5 and x=1
1-there were a huge amount of firsts yesterday
2-first ever inauguration the ex president didn’t go
Answer:
alr so ques is
x3 + 8
x^3 + 2^3
now apply identity of a3 + b3
so finally we get
=(x+2)(x2−2x+4)
option 2
enjoy!!!!!